2011
DOI: 10.1002/ece3.33
|View full text |Cite
|
Sign up to set email alerts
|

Population‐specific demography and invasion potential in medfly

Abstract: Biological invasions are constantly gaining recognition as a significant component of global change. The Mediterranean fruit fly (medfly) constitutes an ideal model species for the study of biological invasions due to its (1) almost cosmopolitan geographic distribution, (2) huge economic importance, and (3) well-documented invasion history. Under a common garden experimental set up, we tested the hypothesis that medfly populations obtained from six global regions [Africa (Kenya), Pacific (Hawaii), Central Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 65 publications
4
51
0
2
Order By: Relevance
“…This is the case, for instance, for offspring mass and number in the scorpion Centruroides vittatus (Brown and Formanowicz 1995), for the juveniles' development and survival in the Mediterranean fruit fly Ceratitis capitata (Diamantidis et al 2011), and for the level of parental care in the Kentish plover Charadrius alexandrinus and the snowy plover C. nivosus (Vincze et al 2013). In earwigs, our results do not only demonstrate that each population is characterised by a specific proportion of females producing two clutches under identical (laboratory) conditions (see also Wirth et al 1998;, but also that the population determines whether and how certain life-history traits differ between initial and terminal clutches.…”
Section: Discussionmentioning
confidence: 99%
“…This is the case, for instance, for offspring mass and number in the scorpion Centruroides vittatus (Brown and Formanowicz 1995), for the juveniles' development and survival in the Mediterranean fruit fly Ceratitis capitata (Diamantidis et al 2011), and for the level of parental care in the Kentish plover Charadrius alexandrinus and the snowy plover C. nivosus (Vincze et al 2013). In earwigs, our results do not only demonstrate that each population is characterised by a specific proportion of females producing two clutches under identical (laboratory) conditions (see also Wirth et al 1998;, but also that the population determines whether and how certain life-history traits differ between initial and terminal clutches.…”
Section: Discussionmentioning
confidence: 99%
“…The larval survivorship of R1 on the artificial diet at all temperatures was significantly higher than that of R2 and could have led to higher metabolic heat within the diet and therefore faster development. To date, little is known of the selective pressures shaping the life history of immature tephritids in geographically isolated locations (Diamantidis et al 2011a, b) and additional research focusing on the selective pressure that shape the life history of immature life stages of the different Ceratitis rosa populations is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Diamantidis et al (2011) found that geographically isolated populations of C. capitata vary in a number of traits (e.g., reproductive patterns, survival, developmental rate, and intrinsic rate of increase). From the literature, it seems that the most cold-tolerant stage for most populations of C. capitata is the third instar with the only well-documented exception being Australia.…”
Section: Discussionmentioning
confidence: 99%